A Comprehensive Evaluation of Rough Sets Clustering in Uncertainty Driven Contexts - Arnold SZEDERJESI-DRAGOMIR (Studia Universitatis Babes-Bolyai: Series Informatica, 2024)
This paper presents a comprehensive evaluation of the Agent BAsed Rough sets Clustering (ABARC) algorithm, an approach using rough sets theory for clustering in environments characterized by uncertainty. Several experiments utilizing standard datasets are performed in order to compare ABARC against a range of supervised and unsupervised learning algorithms. This comparison considers various internal and external performance measures to evaluate the quality of clustering. The results highlight the ABARC algorithm’s capability to effectively manage vague data and outliers, showcasing its advantage in handling uncertainty in data. Furthermore, they also emphasize the importance of choosing appropriate performance metrics, especially when evaluating clustering algorithms in scenarios with unclear or inconsistent data. Received by the editors: 5 March 2024. 2010 Mathematics Subject Classification. 68T37, 68T99. 1998 CR Categories and Descriptors. I.5.3 Pattern Recognition.: Clustering – Algorithms; I.5.3 Pattern Recognition.: Clustering – Similarity measures.